Interpreting Clinical Trials With Omega-3 Supplements in the Context of Ancestry and FADS Genetic Variation - Chilton, Floyd H.; Manichaikul, Ani; Yang, Chaojie; O'Connor, Timothy D.; Johnstone, Laurel M.; Blomquist, Sarah; Schembre, Susan M.; Sergeant, Susan; Zec, Manja; Tsai, Michael Y.; Rich, Stephen S.; Bridgewater, Susan J.; et al. (Frontiers in Nutrition, 2022)
Human diets in developed countries such as the US have changed dramatically over the past 75 years, leading to gene by diet interactions that have altered intermediate molecular phenotypes leading to increased obesity, inflammation, and cardiometabolic dysfunction. Evidence over the past decade indicates that the essential dietary omega-6 (n-6) and omega-3 (n-3) polyunsaturated fatty acids (PUFAs), linoleic acid (LA) and -linolenic acid (ALA), which are predominately supplied by vegetable oils, along with genetic variation to impact numerous molecular and clinical phenotypes. Interactions are particularly relevant with FADS1 and FADS2 genes, which encode key fatty acid desaturases in the pathway that converts LA and ALA to their long chain highly unsaturated fatty acid (HUFA) counterparts. These gene by nutrient interactions affect the levels and balance of n-6 and n-3 HUFA that in turn are converted to a wide array of lipids with signaling roles, including eicosanoid and docosanoid oxylipins and endocannabinoids. With few exceptions, n-6 HUFAs are precursors of pro-inflammatory/pro-thrombotic signaling lipids, and n-3 HUFAs are generally anti-inflammatory/anti-thrombotic. We and others have demonstrated that African ancestry populations have much higher frequencies (versus European-, Asian- or indigenous Americas- ancestry populations) of FADS alleles on a “derived” haplotype that are associated with the efficient conversion of dietary PUFA to proinflammatory n-6 HUFAs. By contrast, an “ancestral” haplotype, carrying alleles associated with a limited capacity to synthesize HUFAs, which can lead to n-3 HUFA deficiency, is found at high frequency in certain Hispanic populations and is nearly fixed in several indigenous populations from the Americas. Based on this rationale, a focused secondary subgroup analysis of the VITAL n-3 HUFA supplementation trial stratifying the data on the basis of self-reported ancestry reveal that African Americans may benefit from n-3 HUFA supplementation, and both ancestry and FADS variability should be factored into future clinical trials design.